2016
DOI: 10.1021/acs.analchem.6b01365
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration and Atomization of Arsane in a Dielectric Barrier Discharge with Detection by Atomic Absorption Spectrometry

Abstract: Atomization of arsane in a 17 W planar quartz dielectric barrier discharge (DBD) atomizer was optimized, and its performance was compared to that of a multiple microflame quartz tube atomizer (MMQTA) for atomic absorption spectrometry (AAS). Argon, at a flow rate of 60 mL min(-1), was the best DBD discharge gas. Free As atoms were also observed in the DBD with nitrogen, hydrogen, and helium discharge gases but not in air. A dryer tube filled with NaOH beads placed downstream from the gas-liquid separator to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…A sensitivity of 0.43 AE 0.01 s ng À1 As was found in an Ar atmosphere which was well comparable to the value reported recently in the common (non-modular) MMQTA with Ar carrier gas (0.48 AE 0.003 s ng À1 As). 18 Even higher sensitivity (0.53 AE 0.01 s ng À1 As) was found in the H 2 atmosphere.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A sensitivity of 0.43 AE 0.01 s ng À1 As was found in an Ar atmosphere which was well comparable to the value reported recently in the common (non-modular) MMQTA with Ar carrier gas (0.48 AE 0.003 s ng À1 As). 18 Even higher sensitivity (0.53 AE 0.01 s ng À1 As) was found in the H 2 atmosphere.…”
Section: Resultsmentioning
confidence: 94%
“…It is well known that controlled addition of oxygen into the MMQTA in the form of either air or pure O 2 enhances the sensitivity of determination of hydride forming elements, especially As and Se. 17,18 Oxygen reacts with excess of hydrogen to produce H radicals that are responsible for efficient hydride atomization as well as protecting free atoms from decay reactions. 3,30 The oxygen demand is dependent mainly on carrier gas composition and atomization temperature.…”
Section: Characterization Of the Aunps Surface By Tem Sem And Edsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an HG-DBD-AFS system was applied to measure ultratrace arsenic in surface water, with a 1 ng/L LOD via 8-fold enrichment in 20 mL sampling volume. Soon after, Kratzer et al used a planar DBD atomizer coupled to HG-AAS to enrich arsenic based on similar principle, and confirmed that arsenic analyte can be retained in the DBD atomizer by the Ar–O 2 discharge and subsequently released by the Ar–H 2 discharge. They also realized a preconcentration efficiency of ∼100%, reaching 10 ng/L LOD via 300 s preconcentration.…”
mentioning
confidence: 98%